Student Academic Resilience Survey in View of Social Support - Khasanah, Nur; Umari, Tri; Khadijah, Khairiyah (CV. Rayyan Dwi Bharata, 2024)
Academic resilience is an individual's ability to persist in completing education even in difficult situations. To maintain stable academic resilience, social support is needed. Social support is an interaction or feedback from other people that shows that the individual is appreciated, loved, respected, cherished, and involved in communication with others. Social support in this research comes from the family, because the family is the main and first person close to the individual. Family attitudes that can be a good predictor of student academic resilience are direction from the family, support, and opportunities for parental involvement for students at risk. Social support plays an important role in increasing academic resilience. The research entitled academic resilience survey in terms of social support, aims to determine the level of student academic resilience and the level of student social support as well as the level of student academic resilience in terms of social support. This research is descriptive quantitative research and matches qualitative research with survey methods. The population of this research is class Then it was matched with qualitative research in the form of interviews with guidance and counseling teachers regarding the implications for guidance and counseling in schools. Data collection was carried out by distributing the academic resilience scale and social support scale, then analyzed using the SPSS Version 25 for Windows program.